Trust motivates funders to participate in Shari’ah crowdfunding - Shifa Mohd Nor,; Noor Azuan Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The fourth industrial revolution has influenced many sector including Islamic Finance. The digital revolution has changed the traditional crowdfunding through the usage of technology with smart applications on mobile phones and websites. Among the advantage of crowdfunding is its accessibility, fast transaction, security, transparency, traceability and many more. Through crowdfunding platforms, financial inclusion groups could be reached. Hence, the demand for Shari’ah crowdfunding increases to fulfil the Muslims developmental needs in providing for projects that are compliant according to Shari’ah. Shari’ah crowdfunding platform such as Shekra, Yomken, Ethiscrowd, Waqfworld, KapitalBoost and many more attempts to realize the needs of Muslim society. These activities utilize the financial technology (FinTech) approach via social media or smartphone apps. Although FinTech is widely used nowadays, there is an issue of trust from the investors in gaining their interest to invest in Shari’ah crowdfunding projects since it is virtual. Hence, this study explores the possibility of funder’s motivation to invest in crowdfunding projects from the perspective of trust. This conceptual study highlights the element of trust from three elements which are calculus trust, relationship trust and religiosity (Islam). For future research, the study on trust from a social capital perspective would add value in contributing to the development of digital economy.